The Use of ChatGPT Feedback on Writing Quality: A Content Analysis of Students’ Writing Assignment - Elviani, Mutia; Liani, Ghustiva (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study investigates the effectiveness of ChatGPT feedback in enhancing the writing skills of semester four students at Business Administration study program, which is mostly as Gen Z and constitute a significant portion of today’s global population. Utilizing a mix-method approach, the research explores both quantitative and qualitative aspects of students’ interactions with ChatGPT in the context of foreign language education. A pre-test and a post-test design were employed, involving six students learning English as a Foreign Language (EFL). Through students writing assignment and questionnaires, the use of ChatGPT and its feedback on students’ writing assignment was employed. Quantitative analysis data was examined using Six Trait Writing Framework. It revealed significant improvements in various aspects of writing, including ideas and content, organization, voice, word choice, sentence fluency and convention based on the feedback from ChatGPT. Qualitative questionnaire results verified the findings since students generally held the most optimistic attitudes toward ChatGPT's ability to increase their writing skill. The study reflects the potential role of ChatGPT as a novel learning tool to increase the writing competence of Generation Z students. Overall, the study highlights the potential of ChatGPT as an innovative educational tool to improve writing skills. The findings underscore the value of incorporating AI-powered technologies into language learning to meet the changing needs of today’s learners. Keywords:‎ ChatGPT, Writing Skills, Language Learning, Educational Technology